STUDY ON ESTIMATION METHOD OF TENSILE STRENGTH OF AIRCRAFT STIFFENED-WELED PLATE - BAI ChengZheng; SONG Xin; SHENG HongWei; SHEN Yang; ZHANG JiaZhen (Jixie qiangdu)
This paper studied methods to predict the tensile strength of stiffened-welded plate structure for civil aircraft welding. Based on the law of elastic modulus in the composite material mechanics,a theoretical formula is proposed to estimate the tensile strength of the aircraft welding plate structure,and through the introduction of the mechanical properties of the welded joints,out of plane moment,long truss shape,skin stress concentration four the coefficient,reflecting the influence of factors on the strength of the welded plate structure. The results show that the theoretical calculation is 3. 81% larger than the experimental value,and the error is small,which proves that the theoretical formula established by this study has certain reliability and correctness. The estimation method can provide a reference for the selection of stiffened-welded plate structure material,the improvement of process performance and the aerospace designers ’ estimated strength value of aircraft stiffened-welded plate structure. In addition,the tensile mechanical behaviors of two groups of welding plate with different welding states were simulated and analyzed by using the finite element method. The results show that the cracking state of the weld has no great influence on the tensile strength of the stiffened-welded plate,and through the finite element stress cloud can be observed in the welding plate of the high stress area,showing the failure process,in the future for the new civil welding wall structure design and selection of preresearch stage. The finite element simulation is used to replace the tensile test of large structural members of aircraft siding,reduce the cycle and cost of pre-research,and improve the efficiency of the test.